The Social Pedagogical Discourse of Modernity. The Politics of Human Rights and International Social Work - Christian Wevelsiep (Budapest International Research and Critics University, 2021)
The basic thesis of this paper is that the helping professions have an indispensable task: to reflect the constitution of society in the context of the perception of the other. This discourse of social pedagogy addresses the conditions under which we encounter each other and under which we recognize each other. It is to be asked to what extent this discourse of social pedagogy could contribute to open the horizons of the common, which have been closed by all conceivable forms of violence. The background of the discourse, mentioned here, is close to the social philosophical discourse of modernity. It reflects the form of modernity in all its moral, social and political dimensions. The social-philosophical reference to the present is accompanied by the indispensable critique of power. It designates stages of reflection of that critique that make possible a theory of society. It thus forms, which is to be shown as aa result, the categorical framework of an analysis that enables a view of the structures of existing power relations. It thematizes the essential approaches to the practical overcoming of these phenomena. For this purpose, it will be reflected by way of introduction which theoretical reference the mentioned discourse has and how it is to be understood in comparison to other discourses - thus, it is first about the connections from social philosophy to social pedagogy (2). Within this framework, it will then be shown that the helping professions have an internal reference to the world, which is of eminent importance for the self-description of the discourse (3). How the language of human rights can be translated into transcultural perspectives of action is a complex question that is answered here from a fundamental anthropological perspective (4).